Perinatal Outcome Following Assisted Reproductive Technology in a Tertiary Hospital - Chowdhury, Tanzeem S; R , Laila; M, Mokarrama (Bangladesh Journal of Obstetrics & Gynaecology, 2026)
Objective: Pregnancies following assisted reproductive technologies have become much more common in tertiary hospitals with neonatal intensive care facilities. The aim of this study is to compare the perinatal outcome of women who conceived through Assisted Reproductive Technologies with who conceived naturally. Method: This retrospective cohort study was conducted in BIRDEM Women and Children Hospital from 1st March 2023 to 31st March 2024. The study population was divided into two groups. Group 1 was the ART pregnancy (In Vitro Fertilization, IVF) group and Group 2 was the naturally conceived group. The perinatal outcome of two groups of women admitted in the hospital during that period of time for delivery was compared. Result: Mean maternal age of ART pregnancy was 33.89+4.86 years, and 29.26+5.32 years in natural pregnancy. Women with ART pregnancy in comparison to natural pregnancy had statistically significant advanced maternal age (> 35yr) (45/110 Vs 26/130; p=0.001); multiple pregnancy (63.6% Vs <1%, p=0.001) and maternal morbidity [hypertensive disorder of pregnancy (40% vs. 23.85%), hypothyroidism (39.09% vs. 13.58%), premature of rupture of membrane (20.91% vs. 9.23%), preterm labor (20.91% vs. 4.61%), obstetric cholestasis (14.54% vs. 1.54%), chronic placental insufficiency (8.18% vs. 0.0%), breech presentation (8.18% vs. 2.3%) and placenta related morbidities (8.17% vs. 0.76%) (p<0.05)]. Between ART pregnancy and natural pregnancy: nean gestational age at delivery was 33.71+2.36 weeks Vs 36.11+2.29 weeks; preterm births (166 /179 Vs 64 /131); mean birth weight (2063+557.89 gm Vs 2605gm+649.44gm); low birth weight (70% Vs 33.59%), NICU admission (59% Vs 25.19%). The differences were statistically significant (p=0.001). Conclusion: ART pregnancies have greater perinatal morbidity than naturally conceived pregnancies Bangladesh J Obstet Gynaecol, 2025; Vol. 40(2): 77-83